Generation of acousto-electrical waves using a source of transverse vibrations - KINH, Nguyen Viet; PAJEWSKI, W. (Archives of Acoustics, 1980)
The paper presents a theoretical analysis of the generation of transverse surface waves, using a linear source of vibrations, placed in the plane in which the generated wave propagates. On the basis of the results of the theory presented, the problem of the generation of a surface wave excited by a source of finite dimensions in the form of piezoelectric plates is considered. This method of wave generation was used for the generation of transverse surface waves on a piezoelectric ceramic and on niobiate and iodate of lithium.